Litera po literze... Projektowanie kroju pisma Europa Familiaris - Bieniasz, Katarzyna (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2019)
This article continues the theme of the author’s MA thesis titled Historical typefaces. The aesthetic qualities of the Cyrillic lettering in the author’s original typeface “Europa Familiaris”. The author discusses the questions of literary inspirations and personal motivations directly connected with the theme of the thesis, like: experience in icon-painting and studying art conservation in Lviv. The article describes major aesthetic models, situating them in historical context, and explains the manner of their transformation. The result of her designing work – the ready typeface – has been described through the angle of the structure of characters as well as major design tasks. The author also analyzes the process of designing a typeface at particular stages, considering the nuances of creative work known to any artist, referring among others to her own experience in painting. She concludes that in terms of method, designing a font does not differ from the work of art conservator, only the tools are different. The text is complete with actual examples of application of the Europa Familiaris typeface and tables showing the secrets of the design work.
Letter by letter... Designing the Europa Familiaris typeface
Keywords: projektowanie; font; czcionka; krój pisma; liternictwo; cyrylica; ikona; design; typeface; lettering; Cyrillic; icon